2001
DOI: 10.1088/0964-1726/10/4/317
|View full text |Cite
|
Sign up to set email alerts
|

Smart nano-machining and measurement system with semiconductive diamond probe

Abstract: We have developed an ultraprecision machining system with an in situ STM function. For this purpose, we have made a semiconductive diamond probe of sufficient hardness to prevent deformation or damage occurring during machining and with a tunnel-current-detecting capability for the fabrication of three-dimensional nano-structures in any material, independent of hardness. In order to realize this system, we first constructed a high-resolution driving system with two single-tube three-dimensional piezoelectric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Properly installed, the smart disc-based damping system can reduce the amplitude of the dominant vibration mode by 86% and greatly enhances the line-width precision of circuit patterns for integrated circuit manufacturing. Unno et al [105] also used a pair of piezoelectric tube-type stack actuators to construct a high-resolution driving system for a semi-conductive diamond probe used in nano-scale machining. This driving system demonstrated a resolution of approximately 20 nm.…”
Section: Article In Pressmentioning
confidence: 99%
“…Properly installed, the smart disc-based damping system can reduce the amplitude of the dominant vibration mode by 86% and greatly enhances the line-width precision of circuit patterns for integrated circuit manufacturing. Unno et al [105] also used a pair of piezoelectric tube-type stack actuators to construct a high-resolution driving system for a semi-conductive diamond probe used in nano-scale machining. This driving system demonstrated a resolution of approximately 20 nm.…”
Section: Article In Pressmentioning
confidence: 99%
“…The use of diamond with extreme mechanical hardness and wear resistance as a probe material is expected to eliminate the problem [32,33]. Several studies of micro/nano fabrication using diamond tips have been reported [34][35][36]. However, machining in the depth range of sub-micrometer has not been investigated owing to the low lever stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we also demonstrated the superiority of semiconductive pyramidal diamond tips for scanning tunneling microscope (STM) as well as a machining tool [6] and diamond AFM probes consisting of a V-shaped diamond cantilever integrated with a pyramidal diamond tip [7][8][9]. However, further improvement in the diamond tip feature is required to achieve the measurements and nanomachining of samples with a high aspect ratio feature or steep sidewall like narrow and deep trenches.…”
Section: Introductionmentioning
confidence: 99%